Akurasi Pendeteksian Berdasarkan Parameter Jarak, Jumlah Obyek dan Kekeruhan Air pada Obyek Bergerak Jentik Nyamuk - Febriansyah, Aan; Surojo, Surojo; Pangestu, Rafif Tri; Karimah, Savira (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
A system for detecting the presence of mosquito larvae can be used as a solution to find out whether the air reservoir is healthy or not. This mosquito larva detection system uses several measuring parameters, including the distance between the object of the mosquito larva and the camera, air turbidity/light conditions, and the number of mosquito larvae in the air protector. From the results of tests carried out on the detection distance parameters, the results showed that the system could detect the presence of mosquito larvae within a distance of 5-15 cm in clear air/bright light conditions with a detection success rate above 80%. In the same test, but with cloudy air/dark light conditions, detection went well but a detection error occurred at a distance of 15 cm, namely the system detected objects other than mosquito larvae as mosquito larvae. This is due to several factors, including the lack of variation in the dataset, the detection system is carried out in real-time (in the form of video capture) and the camera specifications used do not meet the minimum value required by the computing system.